2010
DOI: 10.1111/j.1523-1739.2009.01399.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity Differences between Managed and Unmanaged Forests: Meta‐Analysis of Species Richness in Europe

Abstract: Abstract:Conservation Biology 41In an attempt to provide a state of the art of the effect of forest management on biodiversity, 42we performed a MA comparing the species richness of managed and unmanaged forests in 47Our MA provides basic ecological knowledge needed for conservation and ecologically 48 sustainable forestry. In this paper, we showed that forest management has a negative effect 49 on the biodiversity of forest dwelling species. Because we were aware of the limitations of 50 our MA, we used ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
534
7
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 767 publications
(600 citation statements)
references
References 60 publications
20
534
7
15
Order By: Relevance
“…Ancient trees are already in decline (Paillet et al. 2010; Lindenmayer et al. 2012), and drought can be a major stress contributing to oak tree aging and death (Vera 2000; Allen et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ancient trees are already in decline (Paillet et al. 2010; Lindenmayer et al. 2012), and drought can be a major stress contributing to oak tree aging and death (Vera 2000; Allen et al.…”
Section: Discussionmentioning
confidence: 99%
“…2010; Horak et al. 2014), and large, hollow trees are often disproportionately affected (Lindenmayer et al.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic factors such as forest management practice (Paillet et al 2010) and atmospheric deposition of N and S (van Dobben and de Vries 2010; Lee 1998) can also influence species composition. Strongly decreasing emissions of S and moderately decreasing emissions of N have resulted in decreasing levels of N and S deposition throughout Europe (Benedictow et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Here there are relatively few forest specialists compared with other parts of Europe, and forests are inhabited mainly by generalist species adapted to living in a range of habitat types (Mitchell 2006;Fuller et al 2007;Kelly 2008). Previous studies that used meta-analysis, which rely on data collected during separate studies, to investigate species richness across a number of taxonomic groups have found that species dependent on forests, such as bryophytes and saproxylic beetles are more negatively affected by forest management practices than more generalist species (Paillet et al 2010;Stephens and Wagner 2007;Paritsis and Aizen 2008).…”
Section: Species Diversitymentioning
confidence: 99%
“…The response of species diversity to commercial plantation forests varies across taxonomic groups, and much of the evidence for this variation comes from meta-analyses of independent studies which consider individual taxa separately (Paillet et al 2010;Paritsis and Aizen 2008). Very few studies have used empirical data to investigate the importance of plantation forests for more than one taxon simultaneously.…”
Section: Introductionmentioning
confidence: 99%